Evaluasi Kebijakan Kenaikan Tarif Parkir Tepi Jalan Umum Menurut Perda No 2 Tahun 2012 Tentang Retribusi Jasa Umum di Kota Semarang - Rendra Miswandaru; Puji Astuti; Turtiantoro . (Journal of Politic and Government Studies, 2015)
On the edge of public street parking retribution revenue is the source of the lack of an effective semarang.The public street parking rates based on the region regulation no. 2 on next year ' s general service retribution to be able to provide a change in the distribution of income, that the contribution of public street parking retribution revenue of semarang could increase.These problems arise when the revenue target is not based on the previous year and tended to be stagnant.To uncover problems and objective approach diskriptif m a qualitative researcher on research.The analysis is use deskriptif-kualitatif.The aim of this research is to find meaning, the goal, and the market economy and the implementation of bylaw no 2 / 2009 about 2012 general service retribution income for an increase in public street of semarang.Data obtained used to formulate recommendations as a form of implementation of parking on the road side of the public.The results of research showing that, found in the field there was a policy rate hike parkir the edge of a public road because of this constitutional amendment no. 28 / 2009 on local taxes and retribution, and habit of parking attendats that has been raising rates dilapangan.It is in use the government to raise potential revenue from parkir the edge of a public road.But worse management plus the absence of the balance between the management of parking the edge of public roads and smooth traffic maketh cabuk the weakness of the management of parking in the city of semarang.In order to increase the raise of the edge of the parking fee public streets in semarang city , recommendation that can be given is: the government should be able to recalculating the parking the earning potential of the edge of a public road , and trying to increase facilities and infrastructures to the parking area for the harmony of the .Not only that , there must be balance the management and kelancarancaran traffic with the extra such an activity related institutions , repair mechanism the flow of charges for parking and renewal in a bylaw no 1 year 2004 on the implementation of and levies public parking on the street .